Biodiesel production from a microalgal Chlorella sp. through the technology of in situ trasesterification - Ngoc Mai, Dinh Thi; Thom, Le Thi; Lam, Bui Dinh; Hong, Dang Diem; Phuong, Doan Lan (Academia Journal of Biology, 2012)
Biofuel production is now the focal point of world attention due to rapidly escalating demand for crude oil, major security concerns over supply and the environmental damage associated with crude oil extraction, processing and consumption. In the global energy crisis context, biodiesel attracts increasing attention worldwide and has core advantages over mineral diesel in that it is renewable, biodegradable, clean-burning, non-toxic and carbon neutral with respect to carbon dioxide related climate change. Recently, microalgae have long been identified as a potential feedstock due to their many advantages for biodiesel production. Microalgae produce cellular storage lipids in the form of triacetylglycerols (TAGs) which can be readily converted to fatty acid methyl esters (FAMEs) via a simple chemical transesterification reaction. The production of a fast growing, high lipid strain of algae that can be mass cultivated under controlled and engineered conditions will have overwhelming appeal as an feedstock for biodiesel production. We have successfully isolated local, indigenous strains of microalgae which could be preferable for microalgal lipid culture in biodiesel production. Our key objective is to maximize the cellular lipid content of selected strains of local microalgae which have a high biomass yield in engineered intensive bioreactors, on algal growth in photobioreactors PBRs - the natural choice as microalgae are phototrophic, utilizing light and CO2 for the production of energy and biomass via photosynthesis. The aims of this work are firstly to obtain high quality biodiesel production from a microalga Chlorella sp. through the technology of in situ transesterification. Secondly, the prediction properties of the obtanined Chlorella sp. biodiesel such as specific gravity at 150C, kinematic viscosity at 40oC, flash point, iodine value, cetane numeric value will be compared with biodiesel quality standard of Vietnam. The obtained results suggested that the in situ transesterification technology was a feasible and effective method for the production of high quality biodiesel from marine microalga.